Carmelo Bene e il «progetto-ricerca Achilleide»: dal pre-testo alla voce - Buttigliero, Niccolò (Mimesis Journal, 2022)
Why did Carmelo Bene specifically choose Achilles as the last personality with which to confront himself? Is it possible to identify in the «progetto-ricerca Achilleide»? – a project that encompasses more than a decade of Bene’s opus – his testament? These are the questions that animate and direct the hereby study that attempts to carry out a global reconnaissance of the project, confronted by its intermedial nature. The primary subject of interest is Pentesilea. Ovvero della Vulnerabile invunerabilità e necrofilia in Achille, a text that represents Bene’s poetry debut. The object of analysis is not merely this specific literary work, but also the “pre-texts” which constitute its skeleton: Homer, Statius, Kleist. A rereading of these classics in the light of later Bene’s work, in an attempt to specify the reasons behind a choice. Therefore a reconstruction of the voicing of the text – that is already “aural poetry” by itself – is proposed, passing through various “moments” of the «progetto-ricerca», inspecting all the available reviews, critical texts, and testimonies. There is particular attention given to the «spettacolo-sconcerto» from the year 2000, last of Bene’s opus, a conclusive desertion from the scene in an encounter with the absolute musicality of silence.